RESPONSE OF INTRAUTERINE INFUSION OF LUGOL'S IODINE IN INFECTIOUS REPEAT BREEDING CATTLE - SINGH, LAKHWINDER; GANDOTRA, V K; SINGH, JAGIR; ARORA, A K (The Indian Journal of Animal Reproduction, 2023)
Repeat breeding cows (n=24) with endometritis were divided into four groups of six animals each. In group I(control), sing'..:i infusion of 30 ml sterile distilled water whereas, in groups II, Ill and IV 30 ml of lugol's iodine 0.5(single infusion), 0.25 (single infusion) and 0.1 per cent (double infusion at 24 h interval), respectively, wereadministered intrauterine on the day of estrus. A total of 27 bacterial isolates yielded from the uterine sw~bs ofthese cows before treatment were E.coli (29.6%), Bacillus spp. (25.9%), Klebsiella spp. (22.2%), Streptococcusspp. ( 14.8%) and Staphylococcus au reus (7 .4 % ) . The polymorphonuclear leucocytes (PMNLs) were 6-11 per centin the cellular contents of uterine secretions before treatment in all the groups. The PMNLs increased to 70.6±6.48(group II), 58.58±4.75 (group Ill) and 51.00±7.90 percent (group IV) by 24 h of treatment as compared to 12.00±4.77per cent in group I and remained significantly higher in all the treatment groups upto 72 h. One cow in group I, fivein group II, two in group Ill and none in group IV yielded microbial growth on next estrus post treatment; four cowsin group II and one from group Ill conceived. It is evident from the study that lugol's iodine increased the PMNLinflux in the uterine secretions to combat infection. The best response in terms of clearing infection and conceptionwas achieved with 0.5 percent lugol's iodine which can be used effectively to treat bacterial endometritis.
Keywords: Lugol's iodine; Repeat breeder; Cattle